PENERAPAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KETERAMPILAN MENDESKRIPSIKAN SECARA TERTULIS - Ulfah, Siti Maria (Universitas Islam Darul Ulum, 2016)
This study aims to improve motivation, activity , and the ability to write to implement contextual learning . Strategy research is classroom action research that is carried out in three cycles and each cycle includes planning , implementation , observation , and reflection and Verification . Which is the subject of research was grade II Elementary School Lopang I Sub Kembangbahu Lamongan , while the object is learning to write a description that is included in the lesson Indonesian . The results show the stages in the application of contextual learning can improve the quality of the process and the results of learning to write the description in the second grade students of SD Negeri Lopang I Sub Kembangbahu Lamongan.